Association of RNASET2 Gene Polymorphisms with Decreased Expression and Clinical Characteristics of Severity in Crohn’s Disease - Gonsky, Rivkah (Gastroenterology, 2017)
BACKGROUND & AIMS: Variants in the tumor necrosis factor superfamily member 15 gene (TNFSF15, also called TL1A) have been associated with risk for inflammatory bowel diseases (IBD). TL1A affects expression of multiple cytokines to promote mucosal inflammation. Little is known about the TL1A-response pathways that regulate cytokine expression. We investigated T-cell gene expression patterns to determine the mechanisms by which TL1A regulates cytokine production, and whether these associate with outcomes of patients with Crohn’s disease (CD). METHODS: Peripheral T cells isolated from normal donors were cultured with TL1A. We performed gene expression profile analysis, by RNA sequencing, of subsets of interferon gamma (IFNG)-producing and non-producing cells, purified by flow cytometry. Unsupervised hierarchical clustering analysis was used to identify gene expression differences between these subsets. Ribonuclease T2 gene (RNASET2) expression and methylation were assessed by quantitative trait loci analyses. Clinical characteristics of patients (complications, resistance to therapy, recurrence time) were associated with single nucleotide polymorphisms in RNASET2. We performed motif screening to identify polymorphisms that disrupt transcription factor binding sites. Levels of RNASET2 were knocked down with small interfering RNA in CD4(+) T cells and the effect on protein expression was determined by proteomic analysis and cytokine production. Cell aggregation was measured by flow cytometry. RESULTS: We identified 764 genes with at least a 2-fold difference in TL1A-mediated expression between IFNG-secreting and non-secreting T cells (P<1 × 10(−5)). Many of these genes were located near IBD susceptibility variants. RNASET2 was the only IBD risk-associated gene with greater than 5-fold downregulation in the IFNG-secreting subset. RNASET2 disease risk variants were associated with decreased expression in peripheral and mucosal tissues and DNA hypermethylation in CD patients requiring surgical intervention. RNASET2 disease risk variants were associated in CD patients with more complicated disease or resistance to therapy, defined in part by failed response to treatment, increased length of intestinal resection, shorter time to repeat surgery, and high Rutgeerts score (>2) in post-operative endoscopy. The RNASET2 variant rs2149092 was predicted to disrupt a consensus binding site for the transcription factor ETS within an enhancer region. Expression of RNASET2 correlated with expression of ETS. RNASET2 knockdown in T cells increased expression of IFNG and ICAM1 and induced T cells aggregation. A blocking antibody against LFA1, disrupting the LFA1-ICAM1 interaction, reduced T-cell production of IFNG. CONCLUSIONS: We identified decreased expression of RNASET2 as a component of TL1A-mediated increase in production of IFNG and as a potential biomarker for patients with severe CD. Further study of the role of RNASET2 in regulating mucosal inflammation may lead to development of novel therapeutic targets.